Phosphorus fractions in Brazilian Cerrado soils as affected by tillage - Pavinato, Paulo Sergio; Merlin, Alexandre [UNESP]; Rosolem, Ciro Antonio [UNESP] (Elsevier B.V., 2009)
No-tillage systems lead to physical, chemical and biological changes in soil. Soil fertility is responsive to changes in tillage as it depends on nutrient status, soil water content and biological characteristics. This work aimed to determine long term changes in phosphorus forms and availability in the profile of two tropical soils under conventional and no-till systems, and to discuss the significance of these changes on plant growth and demand for P fertilizers. Undisturbed soil cores with 20 cm in diameter were collected to a depth of 40 cm, accommodated in PVC tubes and taken to a greenhouse, where the experiment was conducted. Two soils were collected in Central Brazil, in areas under Cerrado. Both soils had been cropped for at least 10 years under conventional tillage and no-till. In the greenhouse, pots received phosphorus fertilization or not at 43.7 kg ha(-1), and soybean was grown for 60 days, when soil P fractions were determined. Labile P fractions in the soil profile were not affected by management systems, and there was no accumulation of available P under no-till. A large amount of P added as fertilizer was adsorbed in soil and remained in moderately labile fractions, mainly on uppermost soil layers. Therefore, the phosphate fertilizer has promoted P accumulation on less available fractions in soil, remaining P on the soil after crop harvest. Eventually this phosphorus could migrate to more labile fractions and be available for crops grown in succession. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: No-till; Organic phosphorus; Available phosphorus; Phosphorus fractionation